A Course on Terror Medicine: Content and Evaluations. Issue 1 (11th January 2016) - Cole, Leonard A.; Natal, Brenda; Fox, Adam; Cooper, Arthur; Kennedy, Cheryl A.; Connell, Nancy D.; Sugalski, Gregory; Kulkarni, Miriam; Feravolo, Michael; Lamba, Sangeeta
Abstract: Introduction: The development of medical school courses on medical responses for disaster victims has been deemed largely inadequate. To address this gap, a 2-week elective course on Terror Medicine (a field related to Disaster and Emergency Medicine) has been designed for fourth year students at Rutgers New Jersey Medical School in Newark, New Jersey (USA). This elective is part of an overall curricular plan to broaden exposure to topics related to Terror Medicine throughout the undergraduate medical education. Rationale: A course on Terror Medicine necessarily includes key aspects of Disaster and Emergency Medicine, though the converse is not the case. Courses on Disaster Medicine may not address features distinctively associated with a terror attack. Thus, a terror-related focus not only assures attention to this important subject but to accidental or naturally occurring incidents as well. Methods: The course, implemented in 2014, uses a variety of teaching modalities including lectures, videos, and tabletop and hands-on simulation exercises. The subject matter includes biological and chemical terrorism, disaster management, mechanisms of injury, and psychiatry. This report outlines the elective's goals and objectives, describes the course syllabus, and presents outcomes based on student evaluations of the initial iterations of the elective offering. Results: All students rated the course as "excellent" or "very good." Evaluations included enthusiastic comments about the content, methods of instruction, and especially the value of the simulation exercises. Students also reported finding the course novel and engaging. Conclusion: An elective course on Terror Medicine, as described, is shown to be feasible and successful. The student participants found the content relevant to their education and the manner of instruction effective. This course may serve as a model for other medical schools contemplating the expansion or inclusion of Terror Medicine-related topics in their curriculum. LA Cole, B Natal, A Fox, A Cooper, CA Kennedy, ND Connell, G Sugalski, M Kulkarni, M Feravolo, S Lamba .A course on Terror Medicine: content and evaluations .Prehosp Disaster Med .2016 ;31 (1 ):98 –101 .